Peranan Lohicca Sutta dalam Profesionalisme Guru Agama Buddha Pada Abad 21 - Rendi Ade Saputro; Sukarti (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
The professionalism of Buddhist Religious Education teachers in the twenty-first century faces increasingly complex challenges due to rapid technological development, globalization, and social change. Teachers are not only required to master pedagogical and academic competencies but also to uphold moral integrity and exemplary character in delivering the Dhamma. This article aims to examine the role of the Lohicca Sutta as an ethical foundation for strengthening teacher professionalism within the context of modern Buddhist education. This study employs a qualitative approach through library research, analyzing the Lohicca Sutta together with relevant literature on Buddhist education and teacher professionalism. The findings indicate that the Lohicca Sutta emphasizes the moral responsibility of teachers to transmit the Dhamma with right intention, proper understanding, and genuine concern for the well-being of learners. Values such as compassion, wisdom, honesty, and exemplary conduct serve as core elements of teacher professionalism. Within the twenty-first century context, these ethical principles are highly relevant in guiding Buddhist teachers to fulfil their role as educators, moral guides, and character models amid the rapid flow of information and emerging moral challenges. Thus, the Lohicca Sutta provides an essential ethical and spiritual framework for strengthening the professionalism of Buddhist Religious Education teachers, ensuring that Buddhist education not only develops cognitive understanding but also cultivates moral character and inner awareness among students.